Rancang Bangun Sistem Informasi Manajemen Petugas Penyuluh Dinas Pertanian di Kabupaten Jombang - Muhammad Rifqi Helmi Azhari; Agus Sifaunajah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to develop a Management Information System for Extension Officers at the Jombang Regency Agriculture Office to overcome the obstacles faced in data management and extension reporting that were previously done manually. The designed information system enables more accurate, easy-to-use, and real-time data management, making it easier for extension officers to carry out administrative tasks and increase agricultural productivity. The system also supports the Agriculture Office in monitoring and evaluating extension performance more optimally, as well as strengthening decision-making in agricultural management in Jombang Regency. The results show that the implementation of this system not only improves the work efficiency of extension officers, but also provides an easily accessible solution to improve services and sustainability of the agricultural sector in the area. Recommendations for future research include the integration of the latest technology, improvement of the user interface, and regular system testing and evaluation to ensure the performance and reliability of the system on an ongoing basis.